Travo Quality Control Analysis In Travo Testing Process Using Six Sigma Method And Quality Control Circle (QCC) In PT. Bambang Djaja - Muhammad Huda Alamin; Hana Catur Wahyuni (Universitas Muhammadiyah Sidoarjo, 2021)
Bambang Djaja is an industry engaged in the manufacturing industry. Of course in making this travo there should be no errors but there is a partial defect that can result in failure in the testing process of thevovo, partial defects themselves are caused by adanaya impurities such as insulation attached to components, dust, and other metals. in addition it was also found that there was a process of isolation that was less strong and when brezzing, brezzing was still hollow. The method in this study uses the Six Sigma method and quality control circle. The data collection method uses primary data and secondary data obtained from interviews and data from the company. This method was chosen because it is expected to get maximum results from the research conducted.The results of the research that has been done are increasing the effectiveness and efficiency of work by removing work processes that do not have added value (non value added) so that the production process at PT. Bambang Djaja is getting better, besides this research also has a positive impact on the facilities and infrastructure to support workers